2019
DOI: 10.1259/bjr.20180695
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of contrast-enhanced and unenhanced combined pulmonary artery MRI and magnetic resonance venography techniques in the diagnosis of venous thromboembolism

Abstract: Pulmonary embolism (PE) is a common disorder with high mortality and usually results from deep vein thrombosis (DVT) of lower extremities. 1 Although they represent different aspects of the same process, PE and DVT are generally evaluated with different imaging methods. In current clinical practice, CT pulmonary angiography (CTPA) is used as the first line imaging modality in PE diagnosis, whereas Doppler ultrasonography is the initial modality in the diagnosis of DVT. 2-4 A single reliable test that can accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Similar to those results, the present study determined that true FISP had a specificity of 80.0 and 99.8% on a per-patient basis and per-vessel basis, respectively, and the sensitivity was 81.3% in the per-patient analysis but only 36.7% in the per-vessel analysis. For different levels of the pulmonary arteries, the specificity ranged from 99.6 to 100% irrespective of the location of pulmonary vessels, while the sensitivity decreased ------------------------------------------------- from the central-lobar level (70.7-90.0%) to the segmental level (18.5%) and its ability to depict the peripheral pulmonary vasculature was diminished more than that for the central pulmonary arteries (22), which is in accordance with previous studies (13,23); however, the sensitivity at the segmental level (18.5%) was lower than that determined in previous studies (41.7 and 62.0%). This discrepancy may be due to the different analyses, as a per-vessel analysis was employed to detect the vessels that were involved with emboli at different levels; this discrepancy may also be attributed to different thrombus distributions in different studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to those results, the present study determined that true FISP had a specificity of 80.0 and 99.8% on a per-patient basis and per-vessel basis, respectively, and the sensitivity was 81.3% in the per-patient analysis but only 36.7% in the per-vessel analysis. For different levels of the pulmonary arteries, the specificity ranged from 99.6 to 100% irrespective of the location of pulmonary vessels, while the sensitivity decreased ------------------------------------------------- from the central-lobar level (70.7-90.0%) to the segmental level (18.5%) and its ability to depict the peripheral pulmonary vasculature was diminished more than that for the central pulmonary arteries (22), which is in accordance with previous studies (13,23); however, the sensitivity at the segmental level (18.5%) was lower than that determined in previous studies (41.7 and 62.0%). This discrepancy may be due to the different analyses, as a per-vessel analysis was employed to detect the vessels that were involved with emboli at different levels; this discrepancy may also be attributed to different thrombus distributions in different studies.…”
Section: Discussionsupporting
confidence: 92%
“…The present results initially validated true FISP to be feasible for PE detection in the central and lobar pulmonary arteries, but inadequate for the segmental emboli with only 18.5% sensitivity. It has been reported that the incidence of severe acute adverse reactions associated with gadolinium-based contrast material is lower than that of iodinated contrast agents (24,25), and a large number of clinical studies related to MR for PE diagnosis have been performed using contrast-enhanced MR (12,13,16,23). As contrast-enhanced MRPA is a fast and flow-independent method for assessing pulmonary vasculature, it is able to avoid saturation effects and offer a substantially higher resolution than non-contrast techniques.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, CMRA of the pulmonary arteries should only be considered in at centers that routinely perform it and in patients in whom standard tests (e.g., CTA) are contraindicated. A more recent study that combined a non-contrast and CE protocol found CMR to be practically equivalent to pulmonary CTA in patients with suspected thromboembolism [ 121 ]. Pulmonary artery CMRA remains the technique of choice for integrated cardiopulmonary evaluation of acquired pulmonary artery stenosis [ 122 ], evaluation of pulmonary artery aneurysms [ 123 ] and dissection [ 124 ].…”
Section: Acquired Vascular Diseasementioning
confidence: 99%
“…Radial QISS‐MRA provided a higher sensitivity, specificity, positive/negative predictive value, and accuracy than Cartesian bSSFP‐MRA. In several previous publications, the clinical performance of Cartesian bSSFP‐MRA was evaluated compared to CE‐CTA in two, three, or four pulmonary regions (central, lobar, segmental, and subsegmental) 11,18,42–44 . Some of these publications included a homogeneous patient group with APE and some included a mixture of patients in whom APE was clinically suspected and in those with confirmed APE based on CE‐CTA findings.…”
Section: Discussionmentioning
confidence: 99%